2007
DOI: 10.1002/jcla.20136
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of CA19‐9 in patients with nonmalignant respiratory diseases

Abstract: CA19-9 is a specific tumor marker in patients with gastrointestinal cancer; however, some patients with respiratory disease can have elevated serum levels of CA19-9 as well. In this study we evaluated serum CA19-9 levels of patients with nonmalignant respiratory diseases. We also estimated the prognostic significance of elevated serum levels of CA19-9 in patients with interstitial lung diseases. The study included 554 patients who had been diagnosed at our hospital during the period of 1984-2005. Serum CA19-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 25 publications
1
53
0
2
Order By: Relevance
“…High CA 19-9 elevation has been observed in some chronic inflammatory lung diseases, such as intestinal pneumonia, bronchiectasis, diffuse panbronchiolitis etc [21] . In the present study, CA 19-9 was higher in lung cancer subjects while correlation was not there with CEA and thus it is presumed that elevated serum CA 19-9 was associated with the CA 19-9 generated by cancer cells of lung.…”
Section: Discussionmentioning
confidence: 99%
“…High CA 19-9 elevation has been observed in some chronic inflammatory lung diseases, such as intestinal pneumonia, bronchiectasis, diffuse panbronchiolitis etc [21] . In the present study, CA 19-9 was higher in lung cancer subjects while correlation was not there with CEA and thus it is presumed that elevated serum CA 19-9 was associated with the CA 19-9 generated by cancer cells of lung.…”
Section: Discussionmentioning
confidence: 99%
“…CA19-9 is a tumor marker which is not so specific for malignant tumor, which can be found in the normal epithelial lining of the biliary tract, gastric mucosa and pancreatic duct (1), or even respiratory epithelium (2). Some reports showed that the CA19-9 is also produced by the bronchiolar epithelia, as a result of airway damage; it can be elevated in serum (3).…”
Section: Discussionmentioning
confidence: 99%
“…CA 19-9 is synthesized by normal human pancreatic and biliary ductular cells as well as by gastric, colonic, endometrial, and salivary epithelia [9]. Persistent high serum levels of this cancer marker have also been reported in serum CA 19-9 with no evidence of malignant disease [5] as well as in patients with nonmalignant diffuse lung diseases, such as idiopathic pulmonary fibrosis, bronchiectasis, cystic fibrosis [10] and diabetes mellitus [11]. It has been shown that increased CA 19-9 serum levels are present in patients with hypothyroidism, and the gradual improvement of the thyroid function resulted in the resolution of the elevated CA 19-9 levels [12].…”
Section: Discussionmentioning
confidence: 99%